ChemInform Abstract: Direct Copper‐Catalyzed α‐Arylation of Benzyl Phenyl Ketones with Aryl Iodides: Route Towards Tamoxifen. Issue 19 (18th April 2013) - Danoun, Gregory; Tlili, Anis; Monnier, Florian; Taillefer, Marc
Abstract This is the first efficient α‐arylation of non‐activated deoxybenzoin derivatives with simple aryl iodides.